Thiosocius teredinicola gen. nov., sp. nov., a sulfur-oxidizing chemolithoautotrophic endosymbiont cultivated from the gills of the giant shipworm, Kuphus polythalamius - Altamia, Marvin A. (Microbiology Society, 2019)

(untitled) (Int J Syst Evol Microbiol)
A chemolithoautotrophic sulfur-oxidizing, diazotrophic, facultatively heterotrophic, endosymbiotic bacterium, designated as strain 2141T, was isolated from the gills of the giant shipworm Kuphus polythalamius (Teredinidae: Bivalvia). Based on its 16S rRNA sequence, the endosymbiont falls within a clade that includes the as-yet-uncultivated thioautotrophic symbionts of a marine ciliate and hydrothermal vent gastropods, uncultivated marine sediment bacteria, and a free-living sulfur-oxidizing bacterium ODIII6, all of which belong to the Gammaproteobacteria. The endosymbiont is Gram-negative, rod-shaped and has a single polar flagellum when grown in culture. This bacterium can be grown chemolithoautotrophically on a chemically defined medium supplemented with either hydrogen sulfide, thiosulfate, tetrathionate or elemental sulfur. The closed-circular genome has a DNA G+C content of 60.1 mol% and is 4.79 Mbp in size with a large nitrogenase cluster spanning nearly 40 kbp. The diazotrophic capability was confirmed by growing the strain on chemolithoautotrophic thiosulfate-based medium without a combined source of fixed nitrogen. The bacterium is also capable of heterotrophic growth on organic acids such as acetate and propionate. The pH, temperature and salinity optima for chemolithoautotrophic growth on thiosulfate were found to be 8.5, 34 °C and 0.2 M NaCl, respectively. To our knowledge, this is the first report of pure culture of a thioautotrophic animal symbiont. The type strain of Thiosocius teredinicola is PMS-2141T.STBD.0c.01a(T) (=DSM 108030(T)).